Boron-based hydrogen storage materials towards Power-to-X technology on the path to carbon neutrality - Filiz, Bilge Coskuner; Yoruklu, Hulya Civelek; Acikalin, Korkut; Demirci, Umit B.; Figen, Aysel Kanturk (PERGAMON-ELSEVIER SCIENCE LTD, 2023)
Boron-based energy carrier materials (BEMs) encompass a group of hydrogen storage media, including borohydrides (such as NaBH4 , LiBH4 , and KBH4) and boranes (such as NH3BH3 , CH3NH2BH3 , and (CH3)2NHBH3), which exhibit hydrogen densities ranging from 85 to 125 kg/m3. BEMs serve as essential reducing agents, as well as carriers of hydrogen and heat. They have garnered considerable attention for their potential application in Power-to-X technology, aiming to achieve carbon neutrality by mitigating the greenhouse gas effects associated with fossil fuel emissions. Research findings indicate that BEMs exhibit carbon dioxide (CO2)-to-fuel yield of over 50%, offering an effective means of controlling CO2 emissions when integrated into Power-to-X technologies. Despite the promising advances made in utilizing BEMs for carbon neutralization, their utilization in carbon capture and storage (CCS) are still at an early development stage. Consequently, further investigations are necessary to assess the scalability, effectiveness, and feasibility of these materials. This study investigates these aspects and presents future perspectives based on a comprehensive analysis of relevant literature.(c) 2023 Hydrogen Energy Publications LLC. Published by Elsevier Ltd. All rights reserved.
Keywords: Hydrogenation; Decarbonization; Boron-based energetic materials; Carbon dioxide reduction; Valuable chemicals; FRUSTRATED LEWIS PAIRS; AMMONIA-BORANE; CO2 HYDROGENATION; NICKEL-CATALYST; FORMIC-ACID; SODIUM-BOROHYDRIDE; METAL BOROHYDRIDES; DIOXIDE; REDUCTION; HYDROLYSIS; Chemistry; Electrochemistry; Energy & Fuels